Early-strength geopolymer curing agent and curing method for fluid-state high-plasticity clay

By using early strength geopolymer curing agent in fluid high-plastic clay, the contradiction between flowability and early strength is solved, the cement usage and environmental pollution are reduced, and the efficient curing effect is achieved.

CN119430775APending Publication Date: 2025-02-14GUILIN UNIV OF ELECTRONIC TECH +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411823672.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

Flowing high-plastic clay is difficult to meet the requirements of flowability and early strength at the same time in emergency rescue projects, and traditional cement curing agents have high costs and environmental pollution problems.

Method used

The premature strength geopolymer curing agent is adopted, which consists of the main curing agent, the activater, the premature strength agent and the viscosity reducing agent. Through specific component ratios and process steps, the fluidity of the fluidized high-plastic clay is improved and Early intensity.

Benefits of technology

It significantly improves the fluidity and early strength of fluid high-plastic clay, reduces the amount of cement, reduces environmental pollution, and achieves the effect of achieving the target flow at a lower moisture content.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005183692460000041
    Figure BDA0005183692460000041
  • Figure BDA0005183692460000051
    Figure BDA0005183692460000051
  • Figure BDA0005183692460000061
    Figure BDA0005183692460000061
Patent Text Reader

Abstract

The invention relates to the technical field of geotechnical engineering, and discloses an early-strength geopolymer curing agent for fluid-state high-plasticity clay in order to solve the contradiction that the fluid-state high-plasticity clay needs to maintain enough fluidity and obtain high early strength in the curing process. The curing agent is prepared from the following raw materials in parts by mass: 60-80 parts of a main curing agent, 6-21 parts of an exciting agent, 3-9 parts of an early strength agent and 6-12 parts of a viscosity reducer. The plasticity index of the high-plasticity clay is larger than 20, and the mass of particles with the particle size smaller than 0.005 mm exceeds 30% of the total mass of the clay. Compared with the prior art, the curing agent disclosed by the invention has the advantages that the use amount of water can be reduced while the sufficient flowability of the fluid-state high-plasticity clay is maintained, the early strength of a cured soil body is greatly improved, meanwhile, the use amount of cement can be reduced by utilizing geopolymer curing, solid wastes are recycled, and good economic benefits and environmental protection benefits are achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of geotechnical engineering, and particularly relates to an early-strength geopolymer curing agent for fluid high-plastic clay and a curing method. Technical Background

[0002] Fluidized solidified soil is a new type of building material. It is formed by mixing soil, curing agent, admixture and water in a certain proportion to form a mixture with certain fluidity and a certain strength after solidification. Fluidized solidified soil can be used for backfilling and pouring of various fertilizer troughs, foundation pits, and mine pits. It is also widely used in the reinforcement treatment of road subgrades, building foundations, etc.

[0003] High plastic clay is a fine-grained soil with a plasticity index of more than 20, and the mass of particles with a particle size less than 0.005 mm exceeds 30% of the total mass of the clay. High plastic clay is widely distributed in southwest my country and is often abandoned due to its poor engineering properties. Using high plastic clay to prepare fluidized solidified soil for backfilling foundation pits and roadbeds can turn waste into treasure. However, since high plastic clay has a large range of moisture content to maintain its plasticity, in order to make the fluidized solidified high plastic clay fluid, it must have a higher moisture content than ordinary clay.

[0004] In addition, fluidized solidified soil needs to have good fluidity during construction and reach a certain solidification strength after solidification. However, increasing fluidity and improving solidification strength at the same time are contradictory, because in engineering practice, fluidized solidified soil is often made more fluid by increasing water content, but as the water content increases, the solidification strength of fluidized solidified soil also decreases significantly accordingly.

[0005] In order to solve this contradiction, the strength reduction caused by the increase in water content is generally compensated by increasing the dosage of curing agent. Fluidized solidified soil often uses cement as a curing agent, but cement not only has high production costs, but also produces a lot of dust during the production process, and also emits gaseous pollutants such as carbon dioxide, nitrogen oxides, and sulfur dioxide. Therefore, from the perspective of reducing project costs, rationally developing land resources, and protecting the environment, it is necessary to reduce the amount of cement in fluidized solidified soil.

[0006] Since high plastic clay has the characteristics of high plasticity, the contradiction between maintaining good fluidity and high strength during fluid solidification is more prominent. In addition, cement solidified fluid soil has the characteristics of low early strength, which is not suitable for some emergency rescue projects (requiring high early strength).

[0007] Therefore, in emergency rescue projects, a new type of curing agent must be used for fluid high-plastic clay to resolve the contradiction between good fluidity and high curing strength and to obtain better early strength. Summary of the invention

[0008] The purpose of the present invention is to provide a geopolymer curing agent and a curing method thereof in view of the difficulty of simultaneously satisfying the requirements of high fluidity and high early strength of fluid high plastic clay in emergency rescue projects.

[0009] In order to solve the above technical problems, the technical solution adopted by the present invention is:

[0010] An early strength geopolymer curing agent for fluid high-plastic clay comprises 60-80 parts of a main curing agent, 6-21 parts of an activator, 3-9 parts of an early strength agent, and 6-12 parts of a viscosity reducer.

[0011] The main curing agent includes the following material components in parts by mass:

[0012] 30-40 parts of cement;

[0013] 30-40 parts of mineral powder.

[0014] The exciter comprises the following material components in parts by mass:

[0015] 3.5-15 parts of sodium hydroxide;

[0016] Sodium sulfate 1.5-4 parts;

[0017] 1-2 parts of water glass.

[0018] Furthermore, sodium hydroxide, sodium sulfate and water glass were all of analytical grade.

[0019] The early strength agent comprises the following material components in parts by weight:

[0020] 1.5-4 parts of lithium carbonate;

[0021] 1.5-5 parts of sodium thiocyanate.

[0022] Furthermore, lithium carbonate and sodium thiocyanate were both analytically pure.

[0023] The viscosity reducer comprises the following material components in parts by mass:

[0024] 1.5-2.5 parts of sodium tripolyphosphate;

[0025] 3-6 parts of sodium humate;

[0026] 1-2 parts of sodium metasilicate;

[0027] Zeolite powder 0.5-1.5 parts.

[0028] Furthermore, sodium tripolyphosphate, sodium humate, sodium metasilicate and zeolite powder are all analytically pure.

[0029] Furthermore, the plasticity index of the high-plasticity clay is greater than 20, and the mass of particles with a particle size less than 0.005 mm exceeds 30% of the total mass of the clay.

[0030] Furthermore, the fluidity of the fluid high-plastic clay is greater than 140 mm, the 3-day unconfined compressive strength of the early strength is greater than 500 kPa, and the 7-day unconfined compressive strength is greater than 700 kPa.

[0031] The present invention also provides a method for curing a fluid high-plastic clay with an early-strength geopolymer curing agent, comprising the following steps:

[0032] 1) Weigh the main curing agent according to the mix ratio, put it and the air-dried high plastic clay into the mixer container, turn on the mixer and mix for 5 minutes, then turn off the mixer to obtain a mixture;

[0033] 2) Weigh the viscosity reducer according to the mixing ratio, dissolve it in a certain amount of water and stir evenly to prepare a viscosity reducer solution;

[0034] 3) Weigh the activator according to the mixing ratio, dissolve it in a certain amount of water and stir evenly to prepare an activator solution;

[0035] 4) Weigh the early strength agent according to the mix ratio, dissolve it in a certain amount of water and stir evenly to prepare an early strength agent solution;

[0036] 5) Turn on the mixer and continue to mix the mixture obtained in step 1), then add the viscosity reducer solution obtained in step 2) to the mixture and stir for 3 to 5 minutes, add the activator solution obtained in step 3) to the mixture and stir for 2 to 3 minutes, then add the early strength agent solution obtained in step 4) to the mixture and stir for 2 to 3 minutes, and finally add the remaining water to the mixture and stir for 3 to 5 minutes to obtain fluidized high-plastic clay;

[0037] 6) Using a three-mode 70.7 mm cubic mold, lightly apply a layer of vaseline inside the mold, place a piece of filter paper at the bottom of the mold, and then evenly load the fluid high-plastic clay into the three-mode 70.7 mm cubic mold. Cover the surface of the mold with plastic wrap, and then place it in a curing box and cure it at 20° C. and 95% humidity to the predetermined age.

[0038] Furthermore, the mass of the early strength geopolymer curing agent for the fluid high plastic clay is 12% to 20% of the mass of the high plastic clay.

[0039] The present invention has the following beneficial effects:

[0040] 1. In order to solve the contradiction between fluidity and curing strength, viscosity reducers are now introduced. On the one hand, viscosity reducers can significantly reduce the water content required for high plastic clay to reach the target fluidity. On the other hand, due to the reduction of soil moisture content, the curing strength of high plastic clay will be significantly improved. The specific mechanism of action is as follows:

[0041] a. Sodium tripolyphosphate: Sodium tripolyphosphate allows clay to obtain higher fluidity with less water, making the soil particles evenly dispersed. This is because sodium tripolyphosphate molecules can be adsorbed on the surface of soil particles, and through adsorption, interactions occur to destroy the flocculation between particles, resulting in a fluid with high dispersion and good fluidity. In addition, sodium tripolyphosphate reduces the number of hydration layer molecules through sodium ions, thereby releasing excess adsorbed water, increasing the free water content in the mud, and achieving a water reduction effect.

[0042] b. Sodium humate: There are a certain number of adsorption groups and hydration groups on the molecular chain of sodium humate. These groups can be adsorbed on clay particles, especially at the edges and corners where hydration is poor, and at the same time, the hydration film at the edges and corners of clay particles is thickened. As the hydration film at the edges and corners of clay particles is thickened, the ability of clay particles to form a network structure is weakened, the dynamic shear force and apparent viscosity of the mud are reduced, and the free water contained in the network structure is released, thereby improving the fluidity of the mud. Sodium humate molecules dismantle the network structure formed by clay particles, keeping them in a dispersed state at all times, thereby making the mud thinner from thick, reducing the viscosity and shear force of the mud, and improving the fluidity of the mud.

[0043] c. Sodium metasilicate: It can increase the negative charge on the surface of clay particles in the mud, and use the charge repulsion effect to reduce the viscosity of the mud. This charge repulsion effect also reduces the aggregation between particles, thereby improving the fluidity of the mud. At the same time, sodium metasilicate can increase the double electric layer and zeta potential, increase the repulsive force between particles, and this increased repulsive force helps to reduce the contact and aggregation between particles, thereby reducing the viscosity of the mud and increasing its fluidity.

[0044] d. Zeolite powder: The framework structure of zeolite contains abundant exchangeable cations (such as sodium ions, calcium ions, etc.). These cations can be exchanged with certain cations in the mud that cause gelation (such as sodium, potassium, etc.), thereby changing the ion composition of the solution, weakening the electrostatic attraction between particles, and reducing the degree of gelation.

[0045] 2. Geopolymer solidified soil is a new type of soil solidification technology. It uses geopolymer as a solidifying agent. Geopolymer forms a green inorganic gelling material under the action of an activator. Using geopolymer to solidify high plastic clay can not only reduce the amount of cement, but also effectively improve the early strength of the solidified soil. The activator can provide an alkaline environment for the hydration reaction of cement, mineral powder and other gelling materials, and stimulate the activity of the gelling materials. Its mechanism of action is as follows:

[0046] a. Sodium hydroxide: Adding sodium hydroxide to cement and mineral powder solidified soil can improve the strength of the solidified soil. Its working principle mainly includes the following aspects:

[0047] Hydration reaction: Sodium hydroxide, as an activator, can promote the hydration reaction of active ingredients in cement and mineral powder, such as SiO2 and Al2O3, to generate calcium silicate hydrate (CSH) and calcium aluminate hydrate (CAH) gel. These gel-like hydrates can harden themselves to form a skeleton, while cementing soil particles and filling small gaps between soil to form a stable network structure and enhance soil stability.

[0048] Volcanic ash reaction: Sodium hydroxide can also react with active ingredients in industrial by-products to produce more CAH and CSH gels. These gels can quickly fill soil pores and improve soil microstructure, thereby quickly increasing the strength of the solidified soil.

[0049] b. Sodium sulfate: Adding sodium sulfate to cement and mineral powder solidified soil can improve the strength of the solidified soil. Its working principle mainly includes the following aspects:

[0050] Promote early hydration: Sodium sulfate, as a sulfate activator, can promote the early hydration reaction of active components in cement and mineral powder, such as dicalcium silicate (C2S) and tricalcium aluminate (C3A), to generate hydrated calcium silicate (CSH) and hydrated calcium aluminate (CAH) gel.

[0051] Improve reactivity: The addition of sodium sulfate increases the ion concentration in the system, which is related to the increase in ion concentration during cement hydration, thereby promoting the formation of cement hydration products and improving early strength.

[0052] Improved slag solubility: The addition of sodium sulfate is associated with an increase in pH and a decrease in Ca ion activity, both of which are linked through the silicate solubility limit, thereby enhancing the solubility of slag and promoting the formation of more cementitious products.

[0053] 3. For high plastic clay, adding early strength agent can solve the problem of slow early strength development. Early strength agent is mainly used to accelerate the hydration reaction of cement-based materials. The mechanism of action of sodium thiocyanate and lithium carbonate is as follows:

[0054] a. Sodium thiocyanate: Sodium thiocyanate can increase the early reaction speed of cement because it can accelerate the hydration of mineral components such as tricalcium silicate and tricalcium aluminate in cement. Sodium thiocyanate can react with calcium hydroxide (Ca(OH)2) produced by cement hydration to form calcium thiocyanate, which in turn affects the composition of the hydration product. After sodium thiocyanate reacts with Ca(OH)2, the concentration of Ca(OH)2 in the liquid phase decreases, which helps the formation of hydrated calcium silicate (CSH) and further promotes the hydration of cement.

[0055] b. Lithium carbonate: Lithium carbonate can accelerate the early hydration process of cement, significantly shorten the hydration induction period, and increase the early hydration heat release rate and accumulated heat, which helps to improve the early strength. Calcium sulfoxide is the main hydration product. With the increase of lithium carbonate, the amount, shape and microstructure of Calcium sulfoxide will change. In addition, lithium carbonate neutralizes the acidic groups in the soil, increases the pH value of the solidified soil, improves the reaction environment of cement hydration, and promotes the cement pozzolanic reaction. DETAILED DESCRIPTION

[0056] The present invention will be further described below in conjunction with specific examples. It should be understood that these examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention. The experimental methods in the following examples without specifying specific conditions are usually carried out under conventional conditions or under conditions recommended by the manufacturer.

[0057] Unless otherwise defined, all professional and scientific terms used in the present invention have the same meanings as those familiar to those skilled in the art. The reagents or raw materials used in the present invention can be purchased through conventional channels. Unless otherwise specified, the reagents or raw materials used in the present invention are used in a conventional manner in the art or in accordance with the product instructions. The technical solution of the present invention is further described with specific embodiments.

[0058] The mass fractions of the materials in the comparative examples and embodiments are shown in Table 1:

[0059] Table 1 Material components and mass parts of the examples and comparative examples

[0060]

[0061] Example 1

[0062] A method for curing fluid high-plastic clay with an early-strength geopolymer curing agent comprises the following steps:

[0063] (1) Take a curing agent composed of the following raw materials: 30 parts by weight of cement and 30 parts by weight of mineral powder; take a viscosity reducer composed of the following raw materials: 1.5 parts of sodium tripolyphosphate, 3 parts of sodium humate, 1 part of sodium metasilicate, and 0.5 parts of zeolite powder; take an activator composed of the following raw materials: 5.5 parts of sodium hydroxide, 2.5 parts of sodium sulfate, and 1 part of water glass; take an early strength agent composed of the following raw materials: 1.5 parts of lithium carbonate and 1.5 parts of sodium thiocyanate; and take 73 parts by weight of water;

[0064] (2) 667 parts by weight of high plastic clay (optimum moisture content is 18.4%, plastic limit is 27.8%, liquid limit is 51.7%, and plasticity index is 23.9) are taken, and the high plastic clay, 30 parts by weight of cement, and 40 parts by weight of mineral powder are first added into a mixer container, and the mixer is turned on and mixed for 5 minutes, and then the mixer is turned off to obtain a mixture;

[0065] (3) Weigh 1.5 parts of sodium tripolyphosphate, 3 parts of sodium humate, 1 part of sodium metasilicate, and 0.5 parts of zeolite powder, dissolve them in a certain amount of water, and stir them evenly to prepare a viscosity reducer solution;

[0066] (4) Weigh 5.5 parts of sodium hydroxide, 2.5 parts of sodium sulfate, and 1 part of water glass, dissolve them in a certain amount of water and stir evenly to prepare an activator solution;

[0067] (5) Weigh 1.5 parts of lithium carbonate and 1.5 parts of sodium thiocyanate, dissolve them in a certain amount of water and stir evenly to prepare an early strength agent solution;

[0068] (6) Turn on the mixer and continue to mix the mixture obtained in step 2), then add the viscosity reducer solution obtained in step 3) to the mixture and stir for 3 to 5 minutes, add the activator solution obtained in step 4) to the mixture and stir for 2 to 3 minutes, then add the early strength agent solution obtained in step 5) to the mixture and stir for 2 to 3 minutes, and finally add the remaining water to the mixture and stir for 3 to 5 minutes to obtain fluidized high-plastic clay;

[0069] (7) A three-mode 70.7 mm cubic mold is used, a layer of vaseline is lightly applied to the inside of the mold, a piece of filter paper is placed at the bottom of the mold, and then the fluid high-plastic clay is evenly loaded into the three-mode 70.7 mm cubic mold. The surface of the mold is covered with plastic wrap and then placed in a curing box and cured at 20° C. and 95% humidity to the predetermined age.

[0070] Step (3) in the preparation steps of Example 1 is deleted, and the remaining steps are the preparation steps of Comparative Example 1.

[0071] The test results of Example 1 and Comparative Example 1 are shown in Table 2:

[0072] Table 2 Unconfined compressive strength of Example 1 and Comparative Example 1

[0073]

[0074] Example 1 and Comparative Example 1 are used to verify the effect of the viscosity reducer. Compared with Comparative Example 1, 1.5 parts of sodium tripolyphosphate, 3 parts of sodium humate, 1 part of sodium metasilicate, and 0.5 parts of zeolite powder are additionally added in Example 1. The test results show that the fluidized solidified soil prepared from high plastic clay has a fluidity of 150 mm without using a viscosity reducer and with a water content of 73%. Under the same water content, the addition of a viscosity reducer can increase the fluidity of the high plastic clay from 150 mm to 185 mm.

[0075] The test results show that the viscosity reducer has the following effects: ① The use of viscosity reducer can significantly reduce the cohesion of high plastic clay, thereby improving the fluidity of high plastic clay, and can also make high plastic clay reach the basic requirement of 140mm fluidity at a lower moisture content (<73%); ② Viscosity reducer also has a certain effect on improving the curing strength of high plastic clay. After adding viscosity reducer, the 3d, 7d and 28d unconfined compressive strength increased by 24%, 18% and 14% respectively.

[0076] It can be seen that the introduction of viscosity reducer solves the contradiction between the fluidity and curing strength of high plastic clay, and achieves the effect of ensuring a certain curing strength while improving the fluidity of high plastic clay without increasing the dosage of the main curing agent.

[0077] Example 2

[0078] A method for curing fluid high-plastic clay mixed with an early-strength composite curing agent comprises the following steps:

[0079] (1) Take a curing agent composed of the following raw materials: 35 parts by mass of cement and 40 parts by mass of mineral powder; take a viscosity reducer composed of the following raw materials: 2 parts of sodium tripolyphosphate, 3.5 parts of sodium humate, 1.5 parts of sodium metasilicate, and 1 part of zeolite powder; take an activator composed of the following raw materials: 7 parts of sodium hydroxide, 2.5 parts of sodium sulfate, and 1.5 parts of water glass; take an early strength agent composed of the following raw materials: 1.5 parts of lithium carbonate and 1.5 parts of sodium thiocyanate; and take 73 parts by mass of water.

[0080] (2) 667 parts by weight of high plastic clay (optimum moisture content is 18.4%, plastic limit is 27.8%, liquid limit is 51.7%, and plasticity index is 23.9) are taken, and the high plastic clay, 35 parts by weight of cement, and 40 parts by weight of mineral powder are first added into a mixer container, and the mixer is turned on and mixed for 5 minutes, and then the mixer is turned off to obtain a mixture;

[0081] (3) Weigh 2 parts of sodium tripolyphosphate, 3.5 parts of sodium humate, 1.5 parts of sodium metasilicate, and 1 part of zeolite powder, dissolve them in a certain amount of water, and stir them evenly to prepare a viscosity reducer solution;

[0082] (4) Weigh 7 parts of sodium hydroxide, 2.5 parts of sodium sulfate, and 1.5 parts of water glass, dissolve them in a certain amount of water and stir evenly to prepare an activator solution;

[0083] (5) Weigh 1.5 parts of lithium carbonate and 1.5 parts of sodium thiocyanate, dissolve them in a certain amount of water and stir evenly to prepare an early strength agent solution;

[0084] (6) Turn on the mixer and continue to mix the mixture obtained in step 2), then add the viscosity reducer solution obtained in step 3) to the mixture and stir for 3 to 5 minutes, add the activator solution obtained in step 4) to the mixture and stir for 2 to 3 minutes, then add the early strength agent solution obtained in step 5) to the mixture and stir for 2 to 3 minutes, and finally add the remaining water to the mixture and stir for 3 to 5 minutes to obtain fluidized high-plastic clay;

[0085] (7) A three-mode 70.7 mm cubic mold is used, a layer of vaseline is lightly applied to the inside of the mold, a piece of filter paper is placed at the bottom of the mold, and then the fluid high-plastic clay is evenly loaded into the three-mode 70.7 mm cubic mold. The surface of the mold is covered with plastic wrap and then placed in a curing box and cured at 20° C. and 95% humidity to the predetermined age.

[0086] Step (4) in the preparation steps of Example 2 is deleted, and the remaining steps are the preparation steps of Comparative Example 2.

[0087] The test results of Example 2 and Comparative Example 2 are shown in Table 3:

[0088] Table 3 Unconfined compressive strength of Example 2 and Comparative Example 2

[0089]

[0090] In order to verify the effect of the stimulator, compared with Comparative Example 2, 7 parts of sodium hydroxide, 2.5 parts of sodium sulfate and 1.5 parts of water glass were additionally added in Example 2.

[0091] According to the experimental results, the activator has the following effects: ① The activator provides an alkaline environment for the hydration reaction of cement and mineral powder, significantly improving the early strength. The 3d, 7d and 28d unconfined compressive strengths are increased by 144%, 152% and 145%, respectively; ② The addition of the activator will slightly reduce the fluidity of the high plasticity clay. Compared with Comparative Example 2, after adding 7 parts of sodium hydroxide, 2.5 parts of sodium sulfate and 1.5 parts of water glass in Example 2, the fluidity is reduced from 150 mm to 145 mm. The reason is that under the action of the activator, the activity of the glass surface of the slag is stimulated and begins to dissolve, which has a slight effect on the fluidity.

[0092] Example 3

[0093] A method for curing fluid high-plastic clay mixed with an early-strength composite curing agent comprises the following steps:

[0094] (1) Take a curing agent composed of the following raw materials: 35 parts by mass of cement and 40 parts by mass of mineral powder; take a viscosity reducer composed of the following raw materials: 2 parts of sodium tripolyphosphate, 3.5 parts of sodium humate, 1.5 parts of sodium metasilicate, and 1 part of zeolite powder; take an activator composed of the following raw materials: 10 parts of sodium hydroxide, 3 parts of sodium sulfate, and 2 parts of water glass; take an early strength agent composed of the following raw materials: 1.5 parts of lithium carbonate and 1.5 parts of sodium thiocyanate; and take 73 parts by mass of water.

[0095] (2) 667 parts by weight of high plastic clay (optimum moisture content is 18.4%, plastic limit is 27.8%, liquid limit is 51.7%, and plasticity index is 23.9) are taken, and the high plastic clay, 35 parts by weight of cement, and 40 parts by weight of mineral powder are first added into a mixer container, and the mixer is turned on and mixed for 5 minutes, and then the mixer is turned off to obtain a mixture;

[0096] (3) Weigh 2 parts of sodium tripolyphosphate, 3.5 parts of sodium humate, 1.5 parts of sodium metasilicate, and 1 part of zeolite powder, dissolve them in a certain amount of water, and stir them evenly to prepare a viscosity reducer solution;

[0097] (4) Weigh 10 parts of sodium hydroxide, 3 parts of sodium sulfate, and 2 parts of water glass, dissolve them in a certain amount of water and stir evenly to prepare an activator solution;

[0098] (5) Weigh 1.5 parts of lithium carbonate and 1.5 parts of sodium thiocyanate, dissolve them in a certain amount of water and stir evenly to prepare an early strength agent solution;

[0099] (6) Turn on the mixer and continue to mix the mixture obtained in step 2), then add the viscosity reducer solution obtained in step 3) to the mixture and stir for 3 to 5 minutes, add the activator solution obtained in step 4) to the mixture and stir for 2 to 3 minutes, then add the early strength agent solution obtained in step 5) to the mixture and stir for 2 to 3 minutes, and finally add the remaining water to the mixture and stir for 3 to 5 minutes to obtain fluidized high-plastic clay;

[0100] (7) A three-mode 70.7 mm cubic mold is used, a layer of vaseline is lightly applied to the inside of the mold, a piece of filter paper is placed at the bottom of the mold, and then the fluid high-plastic clay is evenly loaded into the three-mode 70.7 mm cubic mold. The surface of the mold is covered with plastic wrap and then placed in a curing box and cured at 20° C. and 95% humidity to the predetermined age.

[0101] Step (5) in the preparation steps of Example 3 is deleted, and the remaining steps are the preparation steps of Comparative Example 3.

[0102] The test results of Example 3 and Comparative Example 3 are shown in Table 4:

[0103] Table 4 Unconfined compressive strength of Example 3 and Comparative Example 3

[0104]

[0105] Example 3 and Comparative Example 3 are used to verify the effect of the early strength agent. Compared with Comparative Example 3, 1.5 parts of lithium carbonate and 1.5 parts of sodium thiocyanate are additionally added in Example 3. The test results show that when the early strength agent is not used, the 3d and 7d strengths of the fluidized solidified soil prepared by high plasticity clay can reach 38% and 51% of the 28d unconfined compressive strength. After adding 1.5 parts of lithium carbonate and 1.5 parts of sodium thiocyanate as activators, the 3d and 7d strengths of the fluidized solidified soil can reach 50% and 71% of the 28d unconfined compressive strength. At the same time, compared with the solidified soil without early strength agent, the 3d and 7d strengths are increased by 39% and 45% respectively. According to the above results, the early strength agent can make the fluidized solidified soil obtain higher early strength.

Claims

1. An early-strength geopolymer curing agent and curing method for fluid high-plastic clay, characterized in that: Raw materials including the following quality components: 60-80 parts of primary curing agent; 6-21 parts of stimulant; 3-9 parts of early strength agent; 6-12 parts of viscosity reducer.

2. The early-strength geopolymer curing agent and curing method for fluid high-plastic clay according to claim 1, characterized in that: The main curing agent includes the following material components in parts by mass: 30-40 parts of cement; 30-40 parts of mineral powder.

3. The early-strength geopolymer curing agent and curing method for fluid high-plastic clay according to claim 1, characterized in that: The exciter comprises the following material components in parts by mass: 3.5-15 parts of sodium hydroxide; Sodium sulfate 1.5-4 parts; 1-2 parts of water glass.

4. The early-strength geopolymer curing agent and curing method for fluid high-plastic clay according to claim 1, characterized in that: The early strength agent comprises the following material components in parts by weight: 1.5-4 parts of lithium carbonate; 1.5-5 parts of sodium thiocyanate.

5. The early-strength geopolymer curing agent and curing method for fluid high-plastic clay according to claim 1, characterized in that: The viscosity reducer comprises the following material components in parts by mass: 1.5-2.5 parts of sodium tripolyphosphate; 3-6 parts of sodium humate; 1-2 parts of sodium metasilicate; Zeolite powder 0.5-1.5 parts.

6. The early-strength geopolymer curing agent and curing method for fluid high-plastic clay according to claim 1, characterized in that: The plasticity index of the high-plasticity clay is greater than 20, and the mass of particles with a particle size less than 0.005 mm exceeds 30% of the total mass of the clay.

7. The early-strength geopolymer curing agent and curing method for fluid high-plastic clay according to claim 1, characterized in that: The fluidity of the fluid high-plastic clay is greater than 140 mm, the 3-day unconfined compressive strength of the early strength is greater than 500 kPa, and the 7-day unconfined compressive strength is greater than 700 kPa.

8. The early-strength geopolymer curing agent and curing method for fluid high-plastic clay according to claim 1, characterized in that: The following steps are involved: 1) Weigh the main curing agent according to the mix ratio, put it and the air-dried high plastic clay into the mixer container, turn on the mixer and mix for 5 minutes, then turn off the mixer to obtain a mixture; 2) Weigh the viscosity reducer according to the mixing ratio, dissolve it in a certain amount of water and stir evenly to prepare a viscosity reducer solution; 3) Weigh the activator according to the mixing ratio, dissolve it in a certain amount of water and stir evenly to prepare an activator solution; 4) Weigh the early strength agent according to the mix ratio, dissolve it in a certain amount of water and stir evenly to prepare an early strength agent solution; 5) Turn on the mixer and continue to mix the mixture obtained in step 1), then add the viscosity reducer solution obtained in step 2) to the mixture and stir for 3 to 5 minutes, add the activator solution obtained in step 3) to the mixture and stir for 2 to 3 minutes, then add the early strength agent solution obtained in step 4) to the mixture and stir for 2 to 3 minutes, and finally add the remaining water to the mixture and stir for 3 to 5 minutes to obtain fluidized high-plastic clay; 6) Using a three-mode 70.7 mm cubic mold, lightly apply a layer of vaseline inside the mold, place a piece of filter paper at the bottom of the mold, and then evenly load the fluid high-plastic clay into the three-mode 70.7 mm cubic mold. Cover the surface of the mold with plastic wrap, and then place it in a curing box and cure it at 20° C. and 95% humidity to the predetermined age.

9. The early-strength geopolymer curing agent and curing method for fluid high-plastic clay according to claim 8, characterized in that: The mass of the early-strength geopolymer curing agent for the fluid high-plastic clay is 12% to 20% of the mass of the high-plastic clay.